Hartmann and Sesemann. The Critique of Husserl’s Phenomenology and the Problem of Intuition - Jonkus, Dalius (Religija ir kultūra, 2016)
[full article and abstract in Lithuanian; abstract in English]This article deals with the problem of the relationship between intuition and construction. Nicolai Hartmann and Vasily Sesemann understand Husserl’s phenomenology as the practice of intuitive knowledge, which can be contrasted to conceptual construction. Both authors seek to join intuition and conceptual knowledge using the concept of dialectics, or the genesis of knowing. Their positions differ in valuing the relationship between intuition and construction. Hartmann emphasizes the perspective of the natural sciences as a necessary element of knowledge, and Sesemann criticizes scientific knowledge as objectifying and therefore insufficient to understand consciousness and values. Firstly, I discuss how Hartmann understands intuition and construction. Then I analyze how Sesemann explained the irrationality of givenness. Finally, I discuss how both philosophers justify the synthesis of intuition and construction.
Keywords: phenomenology; intuition; Husserl; Hartmann; Sesemann